Anti-nuclear antibody detection in cryoprecipitates: Distinctive patterns in hepatitis C virus-infected patients. Issue 1 (January 2015) - Basile, Umberto; Gulli, Francesca; Torti, Eleonora; De Matthaeis, Nicoletta; Colacicco, Luigi; Cattani, Paola; Rapaccini, Gian Lodovico
Abstract: Background: Anti-nuclear antibodies are immunoglobulins directed against nuclear antigens. They are associated with many autoimmune disorders, but are frequently found in patients infected with hepatitis C virus, possibly indicating an underlying common origin. Likewise, mixed cryoglobulinemia often accompanies autoimmune diseases and hepatitis C infection. Aim: To compare anti-nuclear antibodies and immunoglobulin content of cryoprecipitates from hepatitis C virus-positive patients in order to assess their predictive value in the onset of hepatitis C virus-driven extrahepatic disorders. Methods: Serum from 40 hepatitis C virus-positive patients and 50 controls with rheumatoid arthritis was processed for cryoglobulin detection: all subjects presented with Type III mixed cryoglobulinemia. Immunoglobulin content and immunoglobulin subclasses of cryoprecipitates were assessed by immunofixation and tested by ELISA for rheumatoid factor. Cryoprecipitates were also analysed for anti-nuclear antibodies by indirect immuno-fluorescence to identify specific patterns typical of each condition. Results: Anti-nuclear antibody patterns differed significantly; 26 infected subjects (65%) were IgG3 positive: of these, 25 were also anti-nuclear antibody-positive (96.1%). Conclusions: IgG3 are autoreactive clones unrelated to viral recognition and possibly involved in autoimmune disorders. Altogether, these results may represent useful diagnostic device for early detection of hepatitis C virus-induced autoimmune diseases.